THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND SELF-CONFIDENCE TOWARD SPEAKING ABILITY AT THE SECOND GRADE OF SMPN 4 TOLITOLI - Jaya Jaya (Jurnal Madako Education, 2022)
The objective of this research is to find out the correlation between students’ motivation and self-confidence toward speaking ability at the second grade of SMPN 4 Tolitoli. This research is correlation research. It was conducted at the second grade of SMPN 4 Tolitoli. The researcher used two kinds of instrument to collect the data of the three variables. The first instrument is Kusumaningsih’s questionnaire. It consists of 28 items and 5 point likert scale of students’ motivation and for self-confidence consists of 21 items and 5 point likert scale. This questionnaire used to measure the students’ motivation and self-confidence. The second instrument was speaking test. For the result of speaking ability test, the researcher did not conduct the test by herself. But the result was taken from the teacher of Bahasa Inggris. The technique of collecting the data collection in this research was purposive sampling. In measuring the correlation, the researcher used SPSS 21 program in order to make easy and valid. The finding of this research are first shows the result of the students’ motivation toward speaking ability was  < 0,05. It shows that there was a significant correlation between students’ motivation toward speaking ability. For the value of the coefficient correlation, it has a very weak negative correlation because the value was -0,381. The second, the result of self-confidence toward speaking ability was 0,168 > 0,05. It shows that there was no significant correlation between self-confidence toward speaking ability. For the value of the coefficient correlation, it has a weak negative correlation because the value was -0,250. The last result is students’ motivation and self-confidence toward speaking ability simultaneously was 0,065 > 0,05 it shows that there was no correlation between students’ motivation and self-confidence toward speaking ability at the second grade of SMPN 4 Tolitoli.